Application of the Recitation Method to Improve the Competence of the Medical Laboratory Technology Students in Immunology Field - Patricia Gita Naully; Perdina Nursidika (Pascasarjana Universitas Negeri Malang (UM), 2023)
An accredited mid-level MLT (Medical Laboratory Technology) must have the competence to perform medical laboratory examinations from pre-analytic, analytic, and post-analytic stages in several fields, one of which is immunology. Many D3 MLT students are facing obstacles to passed the immunology course. This obstacle is not only experienced by students of D3 MLT but also by medical students, pharmacy students, and similar majors. The purpose of this research is to determine the effect of recitation method in the form of animation video making and immunology based device on the competence of Diploma 3 (D3) MLT students. This research is a true experimental study with a total sample of 348 students. The average final grade of the experimental class of 2018 and 2019 is 78 and 77, with the passing rate of 93.63% and 96.72%. This result is better than the control class of 2017. It can be concluded that the application of recitation method can improve the competence of MLT students. The assignments given can enhance creativity, students’ interest in immunology courses, and the ability to work well with colleagues or students from other departments or institutions. DOI: 10.17977/jps.v11i12023p012